The novel coronavirus conundrum, the pregnant woman, her child What the obstetrician-gynecologist is learning - Pacheco-Romero, Jose (2020)
The world has changed in the last few months with the appearance of a potentially severe viral disease denominated coronavirus disease 2019 – COVID 19. Initially confused with influenza because of its similar symptoms, it can lead to severe multiorgan complications including acute, deadly pneumonia and damage to the heart, kidneys, liver, bowel, coagulation and nervous system function. The incubation period is 5 to 7 days (range 2 to 14 days); it is more frequent in persons 30 to 79 years old, and less in people under 20. Lethality is about 5% (95% CI 0.5-15%). In this paper, we summarize what is known about its clinical presentation and recommendations from the American College of Obstetricians and Gynecologists, the Royal College of Obstetricians & Gynecologists, the Ministry of Health of Spain and specialized medical institutions and leading journals, on coronavirus disease-19 presentation, prevention and management in pregnant women and their newborns.